1998
DOI: 10.1111/j.1467-8624.1998.tb06210.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermodal Perception of Adult and Child Faces and Voices by Infants

Abstract: This research investigated the ability of 4-and 7-month-old infants to match unfamiliar, dynamic faces and voices on the basis of age or maturity. In Experiment I, infants received videotaped trials of an adult and a child of the same gender, side by side, speaking a nursery rhyme in synchrony with one another. The voice to one and then the other face was played in synchrony with the movements of both faces in a random order across 12 trials. On one block of 6 trials a man and a boy were presented, and on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 66 publications
2
27
0
Order By: Relevance
“…The rationale for a child talker was to increase attention and interest for child participants. Our informal experience with children and formal evidence in infants (Bahrick, Netto, & Hernandez-Reif, 1998) suggest a strong preference for child over adult faces. The recording setting was the Audiovisual Stimulus Preparation Laboratory of the University of Texas at Dallas with recording equipment, sound-proofing, and supplemental lighting and reflectors.…”
Section: Methodsmentioning
confidence: 74%
“…The rationale for a child talker was to increase attention and interest for child participants. Our informal experience with children and formal evidence in infants (Bahrick, Netto, & Hernandez-Reif, 1998) suggest a strong preference for child over adult faces. The recording setting was the Audiovisual Stimulus Preparation Laboratory of the University of Texas at Dallas with recording equipment, sound-proofing, and supplemental lighting and reflectors.…”
Section: Methodsmentioning
confidence: 74%
“…For example, 10‐ to 16‐week‐old infants looked longer to a video clip of an adult speaking a nursery rhyme that maintained lip–voice synchrony compared to an event where the movements of the lips and occurrence of speech were asynchronous by 400 ms (Dodd, 1979). Likewise numerous studies demonstrate within the first 3–6 months of life infants detect differences in temporal audio‐visual synchrony within the context of everyday objects and events (e.g., Bahrick, 1992; Bahrick, Netto, & Hernandez‐Reif, 1998; Lewkowicz, 1992a,b, 1996; Scheier, Lewkowicz, & Shimojo, 2003).…”
Section: Introductionmentioning
confidence: 86%
“…Because older infants process information more quickly than younger infants (Rose, Feldman, & Jankowski, 2002) and have had more experience with the faces and actions of adults, we reasoned that they would show improved ability to detect faces in the context of actions. Further, infants appear to show significant improvement in a variety of related face processing skills between 4 and 7 months of age, including categorization of faces on the basis of gender (emerges at 6 months; Newell & Strauss, 2002), intermodal matching of dynamic faces and voices on the basis of gender (improves from 4 to 6 months; Walker-Andrews et al, 1991), matching specific faces and voices of unfamiliar adults (present at 7 but not 5 months; Bahrick et al, 1998), discriminating the static face of a peer from that of the self (present at 8 but not 5 months; Bahrick et al, 1996), and discriminating affect in dynamic, speaking faces across increasingly more difficult contexts (4-month-olds show audiovisual discrimination, 5-month-olds show auditory discrimination, and 7-month-olds show visual discrimination; Flom & Bahrick, 2007). Experiment 3 thus assessed whether infants of 7 months would discriminate the faces as well as the actions following the short familiarization time (160 s).…”
Section: Methodsmentioning
confidence: 99%
“…This required discriminating the two faces, discriminating the two voices, and detecting a relation between them. Infants of 4 to 8 months of age also match faces and voices on the basis of gender and age (Bahrick, Netto, & Hernandez-Reif, 1998; Patterson & Werker, 2002; Walker-Andrews, Bahrick, Raglioni, & Diaz, 1991). Further, Bahrick and colleagues found that infants discriminated the faces of unfamiliar women engaged in unimodal visual speech by 2 months of age and in bimodal audiovisual speech by 3 months of age (Bahrick, Lickliter, Vaillant, Shuman, & Castellanos, 2004a, 2004b).…”
mentioning
confidence: 99%